Interactive Digital Teaching Materials with Multi-Representation Approach for Deaf Students - Putra, I Made Dwiyana; Sariyasa, Sariyasa; Suarsana, I Made (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2023)
This study aims to (1) create interactive digital teaching materials design with a multi-representation approach to the LCM and GCD for deaf special students of SMPLB; (2) described the results of the prototype of interactive digital teaching materials with a multi-representation approach to the LCM and GCD material for deaf special students of SMPLB; (3) Find out the usability of interactive digital teaching materials with a multi-representation approach to LCM and GCD material for deaf special students of SMPLB. This research uses ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data collection using questionnaires and tests, expert evaluation questionnaires, student response questionnaires, teacher response questionnaires and evaluation test. Data analysis uses qualitative data analysis techniques and descriptive qualitative. This research was conducted at SLB Negeri 1 Buleleng. The product of this research is in the form of interactive digital representation approach that includes LCM and GCD materials, learning videos, exploration learning media, practice exercises, bibliography and developer profiles. Product trial test is carried out limited to feasible, efficient, and effective. e. Final prototype in the form of interactive digital teaching materials that already have feasible, efficient and effective criteria. The format of interactive digital teaching materials in the form of Single site, Website and Epub3 which is packaged on CD. Interactive digital teaching materials already have feasible criteria in terms of the feasibility of teaching materials, good in terms of efficiency and effective in terms of effectiveness. Classical completeness obtained after conducting trials amounted to 87.5%. with the highest value obtained at 93 and the lowest value of 73.